95 MeV neutron scattering on hydrogen, deuterium, carbon, and oxygen - P. Mermod (2018)
Three neutron-deuteron scattering experiments at 95 MeV have been performed recently at The Svedberg Laboratory in Uppsala. Subsets of the results of these experiments have been reported in two short articles, showing clear evidence for three-nucleon force effects. In this paper, we present a more detailed description of the experimental methods as well as further discussion of the results. In addition to neutron-deuteron scattering data, neutron-proton and C12(n,n) elastic scattering data have been measured for normalization purposes, and O16(n,n) data have been obtained for the first time at this energy. It was possible to extract C12(n,n') and O16(n,n') inelastic scattering cross sections to excited states below 12 MeV excitation energy. The inelastic scattering data (for both carbon and oxygen) are shown to have a significant impact on the determination of nuclear recoil kerma coefficients. © 2006 The American Physical Society.